The Daily Routine of the Pile-Dwellers at Ljubljansko Barje (Archaeologia Adriatica, 2020)
Ljubljansko barje is best known in archaeology for the remains of the lives of the pile-dwellers who settled it, albeit with intermissions, from approximately the middle of the 5th until the second half of the 2nd millennium BC. These remains are an exceptional source of information about life in prehistory, and it is planned to carry out interdisciplinary research to enable a relatively reliable insight into the daily routine of the time.
Keywords: Ljubljansko barje; prehistoric pile-dwellings; everyday life; finds